Rational design of mimetic peptides based on promiscuous aldo-ketoreductase enzyme as asymmetric catalysts in aldol and Michael reactions - Bayat, Saadi (2014)
The asymmetric aldol and Michael reactions, as the most prominent carbon-carbon bond formation reactions, are the central study issues in the field of asymmetric synthesis. In this study, promiscuous aldo-ketoreductase (AKR) used to catalyze aldol reaction. between aromatic aldehydes and ketones. Good yield (up to 75%),moderate enantioselectivity (60%), and high diastereoselectivity (dr) up to 93/7 (anti/syn) were obtained. Several mimetic peptides from AKR’s active site were designed and synthesized as asymmetric catalysts in the aldol and Michael reactions. Mimetic peptides PE16aa (1), PH16aa (2), 16aa (3), 8aa (4), 8aa-z (5), 5aa (6), 3aa (7), Fmoc-KLH-R (8), K(z)LH-R (9), PYE (10), PEY (11), PHE (12), PEH (13),LFV (14) 4a and 4b were successfully synthesized using manually solid phase peptide synthesis protocol. Then, all of these mimetic peptides were employed to catalyze aldol reactions and peptides 2, 4, 4a, 4b, 10, 11, 12, and 13 were selected to catalyze Michael reactions. In the aldol and Michael reactions, peptide 4 exhibited the best results (up to 97% yield, up to 99.9% ee and dr up to 99/1). Peptide 1 produced a good yield (88%), moderate enantioselectivity (68%), and excellent diastereoselectivity (dr = 99/1). Peptide 2 afforded the desired anti aldol product in 95% yield, 86% ee and 95/5 dr. Peptide 3 exhibited moderate yield (67%) but poor enantioselectivity (39% ee). Peptide 5 showed good catalytic activity and produced high yield (89%) and enantioselectivity (86%). Pentapeptide 6 catalyzed aldol reaction in high diastereo-and enantioselectivity (dr = 99/1 and 90% ee). PHE showed the best reactivity and selectivity amongst four tripeptides (PYE, PEY, PEH, PHE) up to 94% ee and up to 95/5 dr. Peptide 2 afforded corresponding Michael reaction up to 89% yield, 44% ee, and 99/1 dr. Peptide 4 generated desired Michael product up to 95% yield, 84% ee and 95/5 dr. Mechanism study demonstrated that enamine intermediate and hydrogen-bonding interaction are very important for obtaining high enantiomeric excess. The reusability of peptide 4 as the best catalyst was also conducted for 10 times. Peptide 4 is able to hydrolysis esters in a good to excellent yields of up to 99.7 %. All mimetic peptides exhibited to be active in terms of reactivity and selectivity in c-c bond forming reactions.